(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2026)
This study evaluates the efficacy of Colocynth Citrullus colocynthis extracts (aqueous and alcoholic) in controlling the larvae of Culex pipiens, a common mosquito species and vector for various diseases. The impact of temperature (20-35°C) and salinity (2-8 mS/cm) on the toxicity and effectiveness of these extracts was investigated. The results showed that both extracts demonstrated increased toxicity with higher temperatures and salinity levels. The aqueous extract exhibited a higher toxicity compared to the alcoholic extract, with an LC50 of 0.10 mg/L at 35°C and 8 mS/cm salinity, while the alcoholic extract had an LC50 of 0.19 mg/L under the same conditions. The highest efficiency was observed with the aqueous extract at 35°C, where the degradation rate of larvae was significantly higher. These findings suggest that C. colocynthis extracts could serve as an environmentally friendly alternative to chemical pesticides in mosquito control, with significant potential for use in integrated pest management systems.